Development and psychometric testing of a visual analog scale for dental fluorosis - R Ramya; C G Ajithkrishnan; K Thanveer (Wolters Kluwer Medknow Publications, 2014)
Objectives: The aim was to develop and psychometrically test a visual analog scale (VAS) for dental fluorosis. Materials and Methods: In a cross-sectional study, esthetic perceptions of varying severities of fluorosis in permanent maxillary incisor teeth presented in 36 photographs were graded on a 10 cm VAS by two groups - an expert panel of dental specialists and lay group comprising 1 st year dental students. The photographs were also graded using Thylstrup-Fejerskov index (TFI). Inter and intra-examiner reliability testing and comparison of specialists' and 1 st year students' perceptions were made using intra-class correlation coefficient (ICC). Mean VAS values were validated against TFI scores using Spearman correlation coefficient. Results: A VAS for dental fluorosis was constructed with the help of mean values of subjective ratings for each of the photographs. Inter-rater reliability was found to be moderate (ICC = 0.59). The intra-rater reliability for both the lay group (ICC range: 0.91-0.98) and dental specialists' group (ICC range: 0.87-0.98) was found to be excellent. High correlation was obtained between lay group's and dental specialists' perception of fluorosis on VAS (r = 0.93). VAS scores correlated moderately with TFI scores for the photographs (Spearman's ρ = 0.725). All the findings were found to be statistically significant (P < 0.05). Conclusion: The developed VAS was found to be a valid and reliable tool to assess dental fluorosis. Validation of the scale on a larger sample from the general population is recommended before it is applied in clinical and epidemiological settings.